Inmate Perspectives on the Effectiveness of Prison Labour Programs: A Critical Review of the Literature - Renaud, Alexandre (Université d'Ottawa | University of Ottawa, 2021)
A significant number of federal Canadian inmates have substantial, unaddressed employment needs prior to even setting foot into the penitentiary. This research undertakes a qualitative evidence synthesis to bring to light the experiences of inmates partaking in prison labour as well as their perspectives concerning the rehabilitative value of this work in assisting them to integrate the labour market upon their release. Using a research strategy based on Landry et al.’s (2007) five-step process for conducting a systematic literature review, 15 scholarly articles were retained and their findings relevant to the research topic were synthesized. The results indicate that prison labour programs are useful for attaining a number of objectives, yet the perceived value of these programs for inmates’ professional or personal development is often mitigated. Most notably, this paper raises awareness of the trajectory of marginal employment that often begins prior to incarceration and risks being reinforced through prison labour. The implications of these findings are discussed in light of Hatton’s (2017) framework of invisible work. Keywords: prison work; inmate perspectives; labour market integration; invisible work; qualitative evidence synthesis.